2016
DOI: 10.1159/000443619
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Toothbrushing on the Antierosive Effect of Film-Forming Agents

Abstract: This study evaluated the influence of toothbrushing on the antierosive effect of solutions containing sodium fluoride (225 ppm/F), stannous chloride (800 ppm/Sn), sodium linear polyphosphate (2%/LPP), and their combinations, and deionized water as negative control (C). Solutions were tested in a 5-day erosion-remineralization-abrasion cycling model, using enamel and dentin specimens (n = 8). Erosion was performed 6 times/day for 5 min, exposure to the test solutions 3 times/day for 2min, and toothbrushing (or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
4
17

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 34 publications
(51 citation statements)
references
References 31 publications
(39 reference statements)
0
30
4
17
Order By: Relevance
“…Many studies have shown the improved protection of solutions containing the combination F -+Sn 2+ in comparison with F -for preventing erosion [Schlueter et al, 2009a;Ganss et al, 2010a;Algarni et al, 2015aAlgarni et al, , 2015bScaramucci et al, 2015Scaramucci et al, , 2016. Nevertheless, in the present study, this effect was not so impressive.…”
Section: +contrasting
confidence: 80%
See 4 more Smart Citations
“…Many studies have shown the improved protection of solutions containing the combination F -+Sn 2+ in comparison with F -for preventing erosion [Schlueter et al, 2009a;Ganss et al, 2010a;Algarni et al, 2015aAlgarni et al, , 2015bScaramucci et al, 2015Scaramucci et al, , 2016. Nevertheless, in the present study, this effect was not so impressive.…”
Section: +contrasting
confidence: 80%
“…These polymers have an affinity for, and adsorb to, dental surfaces, forming a protective barrier against erosive acids [Barbour et al, 2005]. Additionally, several studies have shown that some polymers can positively interact with fluorides, improving their protective action [Moretto et al, 2010;White et al, 2011;Scaramucci et al, 2015Scaramucci et al, , 2016Ávila et al, 2017]. Our in vitro data have shown that a linear chain sodium polyphosphate could increase the protection against erosion provided by a solution containing F -and Sn 2+ [Scaramucci et al, 2015], previously known to be effective against erosion [Huysmans et al, 2014].…”
Section: Introductionmentioning
confidence: 61%
See 3 more Smart Citations